Family Caregiving of Aging Adults With Down Syndrome. Issue 2 (21st April 2016) - Hodapp, Robert M.; Burke, Meghan M.; Finley, Crystal I.; Urbano, Richard C.
Abstract: Although persons with Down syndrome now live to approximately 60 years, the implications of increased longevity on family caregiving have received inadequate attention. Even compared with adults with other types of intellectual disabilities, by their late 40s and 50s adults with Down syndrome often show multiple health problems, cognitive‐adaptive declines, and changes in daily work and activities. If alive, their parents are more often elderly, as mothers give birth to newborns with Down syndrome at a median age of 32 years (with high percentages age 40 and older). In addition, higher percentages of adults with (vs. without) Down syndrome live in their family homes and greater percentages may ultimately reside with siblings. Compared with caring for other adults with intellectual disabilities, aging adults with Down syndrome may present earlier—and possibly more severe and more health‐related—caregiving challenges to their parents and siblings. As a field and as a society, the authors note that we need to promote revisions of family support policies and interventions; recognize the inter‐relations of aging‐related changes and their effects; and anticipate how aging‐related changes in the brother–sister with Down syndrome and the parent(s) might affect sibling caregivers.